PROFITABILITAS DAN LEVERAGE SEBAGAI PEMODERASI PENGARUH KEBIJAKAN DIVIDEN PADA NILAI PERUSAHAAN - Octaviani, Ni Kadek Dewi; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The value of the company can deliver maximum shareholder wealth when the company's stock price to rise. The higher the stock price, the higher the wealth of shareholders. This study aims to demonstrate empirically the effect of dividend policy on the value of the company in moderation by profitability and leverage. The population in this study are 155 companies listed in the Indonesia Stock Exchange from 2012 to 2014 year. The sampling technique used was purposive sampling, so he found the number of observations were 48 observations that meet the criteria of the sample. The data analysis technique used to test the hypothesis in this study is a simple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that the dividend policy has positive effect on the value of the company, profitability strengthening effect on the value of the company's dividend policy, and strengthen the leverage effect of dividend policy on the value of the company.
Keywords: Profitability, Leverage, Dividend Policy, and Firm Values